2018
DOI: 10.1200/jco.2018.78.1492
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Deficiency As a Function of Radiation Dose to the Hypothalamus and Pituitary in Pediatric and Young Adult Patients With Brain Tumors

Abstract: Median hypothalamic and pituitary radiation dose, younger age, and longer follow-up time were associated with increased rates of endocrinopathy in children and young adults treated with radiotherapy for brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
108
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 40 publications
14
108
2
4
Order By: Relevance
“…As would be anticipated, the risk for developing primary hypothyroidism appears to be markedly decreased after craniospinal proton irradiation. In a recent large study, Vatner et al[59] found that only 3 (3%) patients treated with craniospinal irradiation developed primary hypothyroidism; all of these cases were compensated in nature and they had thyroid radiation doses similar to children without hypothyroidism. Although Eaton et al[60] did not distinguish the exact nature of hypothyroidism in a study of 77 children with standard risk medulloblastoma, they did find a significantly reduced risk of hypothyroidism in patients treated with protons compared with photons (23 vs. 69%).…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…As would be anticipated, the risk for developing primary hypothyroidism appears to be markedly decreased after craniospinal proton irradiation. In a recent large study, Vatner et al[59] found that only 3 (3%) patients treated with craniospinal irradiation developed primary hypothyroidism; all of these cases were compensated in nature and they had thyroid radiation doses similar to children without hypothyroidism. Although Eaton et al[60] did not distinguish the exact nature of hypothyroidism in a study of 77 children with standard risk medulloblastoma, they did find a significantly reduced risk of hypothyroidism in patients treated with protons compared with photons (23 vs. 69%).…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…In the study by Vatner et al[59], the cumulative incidence of central hypothyroidism was 18%, which represented the second most common endocrinopathy. Eaton et al[60] also published their endocrine outcomes after proton therapy in 40 patients with medulloblastoma.…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, larger radiotherapy boost volumes and higher dose have been linked to declining intellectual trajectory . Dose‐response relationships have been observed for cochlear, endocrine, and cognitive outcomes …”
Section: Introductionmentioning
confidence: 99%
“…8 Dose-response relationships have been observed for cochlear, endocrine, and cognitive outcomes. [9][10][11] For patients with high-risk disease, limiting the boost target volumes to the tumor bed is not well established. Radiotherapy boost to the entire PF remains the most commonly employed strategy for children with high-risk disease.…”
Section: Introductionmentioning
confidence: 99%